An Integrative Analysis of Therapeutic Communication, Nurse Competence, and Nursing Service Quality on Patient Satisfaction in Primary Health Care Centers: A Literature Review - Hasniati Hasniati; Iwan Ardian; Muh. Abdurrouf; Wahyu Endang Setyowati (Indonesian Journal of Global Health Research, 2026)
Patient satisfaction is a key indicator of service quality in primary health care centers. However, it remains influenced by suboptimal therapeutic communication, nurse competence, and the quality of nursing care. Empirical evidence regarding the relationships among these factors is still fragmented and lacks integration. This literature review aims to analyze the influence of therapeutic communication, nurse competence, and the quality of nursing care on patient satisfaction in primary health care settings. A systematic search was conducted in PubMed, ScienceDirect, Google Scholar, and DOAJ for studies published between 2020 and 2025, following the PRISMA 2020 guidelines. The search strategy was guided by the PICO framework using the keywords “Nurse Competence,” “Patient Satisfaction,” “Primary Health Care Centers,” “Service Quality,” and “Therapeutic Communication.” Inclusion criteria comprised original research articles with cross-sectional designs involving healthcare patients and examining therapeutic communication, nurse competence, service quality, and patient satisfaction. A total of 1,972 articles were initially identified, of which 524 duplicates were removed. After the screening process, 15 articles met the inclusion criteria. Study quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool. All included studies demonstrated a statistically significant association between therapeutic communication, nurse competence, and the quality of nursing care with patient satisfaction (p < 0.05). Service quality emerged as the dominant factor, mediating the relationship among variables. Patient satisfaction is influenced by the integration of therapeutic communication, nurse competence, and service quality. Strengthening these three aspects is essential to improve the quality of care in primary health care centers.